Develop Bactra system to determine Mutagens in the Environment, Food / IV modified Mutagens use of hydroxylamine - Baghdad Science Journal (مجلة بغداد للعلوم)
Use Almtafr axis to study the response component that isolates gave a positive response to the use of standard Almtafr which leads to lower the temperature and the number of cells at a temperature suitable Rifampicin resistant less than that TJ and similarly reflected on the frequency of mutations induced